Pengaruh Green Product, Green Promotion dan Green Price Terhadap keputusan Pembelian Konsumen Starbucks Coffee Malang (Studi Kasus Pada Konsumen Starbucks Coffee Malang) - Haris Rizqi Pratama; Siti Asiyah; Alfian Budi Primanto (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract The purpose of this study was to determine and analyze the effect of green product, green promotion and green price on purchasing decisions of Starbucks coffee consumers (a case study on consumers of Starbucks Coffee Malang). This study used a quantitative research method using a questionnaire with a Likert scale of 1-5. The population in this study were all consumers who had been to Stabucks Coffee Malang. The data collection technique uses nonprobability sampling technique, namely purposive sampling technique. The sample in this study amounted to 50 respondents. Data analysis techniques used research instrument tests, classical assumption tests, multiple regression analysis tests, f tests and t tests and coefficient of determination tests. As a data collection material that was analyzed with the help of IBM SPSS Statistics software. The results of this study indicate that green product has a significant effect on purchasing decisions, green promotion has a significant effect on purchasing decisions and green price has no significant effect on purchasing decisions. Keywords: Green Product, Green Promotion, Green Price, and Purchase Decision